Analysis Of The Impact Of Teaching Campus Program In Developing The Skills Of Chemistry Education Students At Maritime Campus - Fitriani Putri; Natasha Febiana; Amanda Pohan Anggi; Solafide Hutajulu Ezra (SHS Web of Conferences)
A teacher's ability to deliver subject matter is a major factor in the success of the knowledge process provided to students. In creating the best learning, teachers must have a number of competencies such as pedagogical competence, personality competence, social competence and professional competence. However, the problem of teacher competence has become a deep issue at various levels of education, especially in maritime areas. Therefore, the Teaching Campus is present as a solution in developing teacher competencies in students as prospective teachers. The purpose of this study is to see the success of the Teaching Campus in an effort to develop teacher competence in Chemistry Education students. This research is a quantitative research with a questionnaire method. The results showed that the development of pedagogical competence, personality competence, social competence, and professional competence gained about 95% overall. This percentage caused all respondents to recommend the Teaching Campus to be followed by other students. Therefore, the Merdeka Campus should continue to be run to develop student competencies as prospective teachers in order to build better Indonesian education.